Non Traumatic Sub Dural Haemorrhage Following Long Term Oral Contraceptive Use - Kumar, Lohith; Raheel, Shadab; Kumar, Chetan; Yadav, Abhishek; Kishor, Upender; Kumar , Anil (Journal of Indian Academy of Forensic Medicine, 2014)
Unusual and accidental findings are sometimes very confusing for Forensic experts to interpret particularly when proper history and treatment records are not available. It often leads to wrong interpretation and miscarriage of justice. The case reported is of an elderly female with history of intermittent fever, found unconscious at home and declared brought dead in casualty. The post-mortem findings showed the presence of subdural haemorrhage in left parieto-occipital region, which raised suspicion of blunt trauma to head. However there was absence of any scalp/skull injuries. The detailed history revealed long term use of oral contraceptive pills by the deceased. The cause of death was concluded as spontaneous subdural haemorrhage, as a complication of long term use of oral contraceptives. This case report highlights the importance of referring previous medical records and history taking before the autopsy in unusual cases which will eliminate most of doubts and also helps in corroborating the findings at autopsy.